Distributed leadership: A model for student leadership engagement - Haniff, N.; Daya, P. (South African Journal of Higher Education, 2023)
Developing student leadership has never been more demanded of higher education institutions than within a 21st century VUCA (volatile, uncertain, complex and ambiguous) world. Globally, there is an increasing preference for organisations to become more devolved and operate more collaboratively (Hayward 2015). Rapid socio-economic changes and enhanced access to higher education, have seen 21st century institutions around the world facing major challenges to their governance systems, curriculum, external relations, research and financing (Jones and Harvey 2017; Black 2015; Jones 2014; Shin and Harman 2009). South African higher education institutions have not escaped these global challenges but the issues have been further exacerbated by the legacy of apartheid and demands for political redress, transformation and equal access (Habib 2016; South African Civil Society Information Services 2013). Such issues are unique to the South African higher education landscape and are demonstrated in the frustrations of the country’s youth, which are regularly being played out on our streets and university campuses. This study sought student leaders’ opinion on their role in participative institutional governance using distributed leadership as the underpinning model.